Water pollution control in developing countries - International Conference on Water Pollution Control in Developing Countries (1978 : Bangkok); Ouana, E. A. R.; Lohani, B. N.; Thanh, N. C.; International Association on Water Pollution Research; International Water Resource Association (Bangkok : Asian Institute of Technology, 1978)
10